Influence of chitosan’s purification methodology on the formation of layer-by-layer films - Pontes, Ana Cristina Facundo de Brito; Nascimento, Luciana Araújo; Pontes, Daniel de Lima; Oliveira, Ótom Anselmo de; Nascimento, Francisco Ordelei da Silva; Silva Júnior, Francimar Lopes da (Eclética Química, 2024)
Concern for the environment for the development of new biodegradable materials has been constant in scientific circles. With this in mind, this work proposes a study on the formation of self-assembled thin films using chitosan (Qt), a biodegradable material. This polyelectrolyte has several purification methodologies, but we did not identify any studies on the effect of these methodologies on film formation. Thus, after the purification process and characterization of the three forms of chitosan purification, films were produced using the layer-by-layer (LBL) technique. The growth of the films was monitored using the UV-vis technique. Spectroscopy in the Infrared region showed positions in the main bands present in chitosan and sodium nitroprusside (NP) in the formed films. Two semi-reversible processes were found for the QtN/NP and QtAc/NP films, related to the reduction of iron oxide present in the NP. The effect of pH (4.0, 7.0 and 10) on the electrochemical processes indicated that the charge transfer occurs more efficiently at pH 7.0.